Forms and Functions of Illocutionary Acts in the Indonesian Presidential Candidate Debate 2024 - Anisa, Salma Kurnia; Lailiyah, Nur; Sujarwoko, Sujarwoko (English Education Department STKIP Agama Hindu Singaraja, 2025)
The presidential debate is a crucial moment in the democratic process, where candidates convey their vision, mission, and work programs directly to the public. This study aims to analyze the form and function of illocutionary speech acts in the Indonesian presidential candidate debate in 2024. The approach used is descriptive qualitative with the theoretical basis of pragmatics, in the category of speech act forms using the theory of Ibrahim (1993), while the category of speech act functions using the theory of Yule (2006). The data were obtained from the transcript of the presidential debate broadcast by the General Election Commission (KPU RI) through the official YouTube channel. This research focuses on three sessions, namely, the first, third, and fifth debates involving the three presidential candidates. The analysis shows that there is a variety of categories of forms and functions of illocutionary speech acts. Among these categories, commissive speech acts are most dominantly used, showing the candidates' efforts to build political commitment and shape their self-image before the public. The findings confirm the importance of the strategic function of speech acts in political communication and contribute to the study of pragmatics and political discourse in Indonesia